The effect of constitutive root isoprene emission on root phenotype and physiology under control and salt stress conditions - Manuel Bellucci; Mohammad Golam Mostofa; Sarathi M. Weraduwage; Yuan Xu; Mostafa Abdelrahman; Laura De Gara; Francesco Loreto; Thomas D. Sharkey (Plant Direct)
Abstract Isoprene, a volatile hydrocarbon, is typically emitted from the leaves of many plant species. Given its well‐known function in plant growth and defense aboveground, we examined its effects on root physiology. We used isoprene‐emitting (IE) lines and a non‐emitting (NE) line of Arabidopsis and investigated their performance by analyzing root phenotype, hormone levels, transcriptome, and metabolite profiles under both normal and salt stress conditions. We show that IE lines emitted tiny amounts of isoprene from roots and showed an increased root/shoot ratio compared with NE line. Isoprene emission exerted a noteworthy influence on hormone profiles related to plant growth and stress response, promoting root development and salt‐stress resistance. Methyl erythritol 4‐phosphate pathway metabolites, precursors of isoprene and hormones, were higher in the roots of IE lines than in the NE line. Transcriptome data indicated that the presence of isoprene increased the expression of key genes involved in hormone metabolism/signaling. Our findings reveal that constitutive root isoprene emission sustains root growth under saline conditions by regulating and/or priming hormone biosynthesis and signaling mechanisms and expression of key genes relevant to salt stress defense.